Circular economies in an unequal world : waste, renewal, and the effects of global circularity - O'Hare, Patrick; Rams, Dagna (Bloomsbury Academic, 2024)
"This landmark first anthropological volume on the topic of 'circular economies' brings together a range of international scholars with regional specialisations in Europe, Africa, Asia, and South America to examine the concept's global implications. Aspirations towards circular economies have become increasingly prominent around the world, with the EU adopting an ambitious 'circular economy action plan', and China enshrining its own circular economy (xunhuan jingji) in law since 2008. Yet until now, social anthropology has largely neglected the potentially deep social impacts of this concept, focusing instead on metrics of waste, despite its obvious implications through every level of the economy and society. This volume covers a diverse array of international actors, including waste-pickers, traders and policymakers, and the global movement of materials like gold, plastic and textiles. Through ethnographic and qualitative case studies, it exposes many of the tensions that exist between state and corporate ideals of the circular economy, and the vernacular practices and philosophies that exist around the world. Contributors examine the frictions that emerge as these concepts and materials travel across different geographic contexts, and ask - what can an anthropological analysis contribute to a concept that is increasingly reshaping economies and restructuring global flows of virgin commodities, recyclables, and waste?"--